Finite element analysis for testing safety-belt anchorages. Issue 1 (1st March 2022) - Manea, A M; Iozsa, M D; Stan, C; Ioniţă, A
Abstract: The passive safety of the vehicle is ensured by designing optimized restraint systems to protect the occupants during the accident. The safety-belts have the role of restraining the occupants of the car on the seat during an impact or in the event of a rollover. Their retention prevents or minimizes the impact between the occupants and the interior components of the passenger compartment. Two simplified models of seat structures are proposed to determine the strength of the safety-belts anchorages. The test of the anchorage for safety-belts of the two seat models is performed in accordance with Regulation no. 14 UNECE. For the two seat models, a three-dimensional resistance structure was made. The 3D models of the seats were inserted in the FEA software. The analysis of the models is done by the finite element method with the Static Structural module of the FEA software. A tensile force is applied during the test on the safety-belts anchorages. The traction force shall be applied in the direction corresponding to the seating position, at an angle of 10°±5° above the horizontal, in a plane parallel to the median longitudinal plane of the vehicle. During the tests the safety-belt anchorages shall withstand the entire period of application of the traction force and the upper safety-belt anchorage shall not be displaced during the test forward of a transverse plane passing through the R point of the seat.